Artificial Diiron Enzymes with a De Novo Designed Four‐Helix Bundle Structure. Issue 21 (6th July 2015) - Chino, Marco; Maglio, Ornella; Nastri, Flavia; Pavone, Vincenzo; DeGrado, William F.; Lombardi, Angela
Abstract: A single polypeptide chain may provide an astronomical number of conformers. Nature selected only a trivial number of them through evolution, composing an alphabet of scaffolds, that can afford the complete set of chemical reactions needed to support life. These structural templates are so stable that they allow several mutations without disruption of the global folding, even having the ability to bind several exogenous cofactors. With this perspective, metal cofactors play a crucial role in the regulation and catalysis of several processes. Nature is able to modulate the chemistry of metals, adopting only a few ligands and slightly different geometries. Several scaffolds and metal‐binding motifs are representing the focus of intense interest in the literature. This review discusses the widespread four‐helix bundle fold, adopted as a scaffold for metal binding sites in the context of de novo protein design to obtain basic biochemical components for biosensing or catalysis. In particular, we describe the rational refinement of structure/function in diiron–oxo protein models from the due ferri (DF) family. The DF proteins were developed by us through an iterative process of design and rigorous characterization, which has allowed a shift from structural to functional models. The examples reported herein demonstrate the importance of the synergic application of de novo design methods as well as spectroscopic and structural characterization to optimize the catalytic performance of artificial enzymes. Abstract : The de novo design of nature‐inspired four‐helix bundle metalloproteins is discussed. Special attention is given to the rational refinement of structure/function in diiron–oxo protein models from the due ferri family, which has allowed a shift from structural to functional models.